Pengaruh Fermentasi Laktat terhadap Kandungan Fenolik Total dan Aktivitas Antioksidan Poliherbal TBR serta Uji Profil Lipid secara in Vivo - Mutti, Annisa Aulia; Kintoko, Kintoko; Sulistyani, Nanik (Syntax Literate, 2025)
Lactate fermentation, such as yogurt, is known to increase antioxidant activity. In addition to yogurt, fermentation can also be applied to herbal plants. Polyherbal plants Taxus sumatrana (Sumatran cypress), jixueteng (Spatholobus suberectus), and pearl grass (Hedyotis corymbosa) (TBR) contain total phenolic compounds that act as antioxidants and can lower cholesterol levels. This study aims to analyze the effect of TBR polyherbal fermentation on total phenol content and antioxidant activity. Polyherbal extraction is carried out by the maceration method using 96% ethanol for 24 hours. Total phenolic tests were carried out using gallic acid, followed by aerobic fermentation with lactic acid bacteria Streptococcus thermophilus and Lactobacillus bulgaricus with 1%, 2%, and 3% TBR extract concentrations. Antioxidant activity was measured by the DPPH method, and lipid profile tests were performed in vivo on 35 white rats (Rattus norvegicus), which were divided into 7 treatment groups. The results showed that TBR polyherbal fermentation significantly increased the total phenolic levels, with a concentration of 3% resulting in the highest levels (41.689 ± 0.5682% GAE). Although antioxidant activity decreased slightly after fermentation, it remained in the strong category (IC50 76.816–88.283 μg/mL). In vivo tests showed that polyherbal yogurt TBR 3% lowered triglyceride and total cholesterol levels and slightly increased HDL levels, but was less effective in lowering LDL. In conclusion, TBR polyherbal fermentation increases total phenolic levels while maintaining strong antioxidant activity, with potential as a natural source of antioxidants for lipid profile improvement.